The development of cartesian product operation of product fuzzy graphs and its properties - Firmansah, Fery; Tasari, Tasari; Yuwono, Muhammad Ridlo (Desimal: Jurnal Matematika, 2025)
The product fuzzy graph is an extension of the fuzzy graph definition by replacing the minimum operation with the product operation. This research is qualitative research with research stages consisting of determining open problems, constructing new definitions, constructing new properties as theorems, and verifying results in the form of mathematical proofs. The purpose of this research is to get the Cartesian product definition of the product fuzzy graph and its properties. The results showed that the Cartesian product of two product fuzzy graphs is a fuzzy graph, the Cartesian product of two strong product fuzzy graphs is a strong product fuzzy graph, and the resulting Cartesian product of two complete product fuzzy graphs is a strong product fuzzy graph. Thus, the novelty of this research is that new properties of product fuzzy graphs are obtained.